METTL16 predicts a favorable outcome and primes antitumor immunity in pancreatic ductal adenocarcinoma - Lu, Liting; Zheng, Dandan; Qu, Junchi; Zhuang, Yanyan; Peng, Juanfei; Lan, Sihua; Zhang, Shineng; Huang, Fengting (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic carcinogenesis is a complicated and multi-step process. It is substantially assisted by N6-methyladenosine (m6A) RNA modification, especially when mutations of driver genes (KRAS, TP53, CDKN2A, and SMAD4) occur. However, the underlying mechanism remains obscure. In this research, we identified m6A regulators as potential biomarkers when mutations of driver genes occur and investigated the role of these m6A candidates in pancreatic ductal adenocarcinoma (PDA). We first estimated the abnormal expression patterns of potential m6A regulators when all the driver genes are mutated using The Cancer Genome Atlas and Gene Expression Omnibus databases. METTL16, an m6A"writer", was chosen as a unique candidate of PDA owing to its markedly differential expression under mutations of all driver genes (KRAS, TP53, CDKN2A, and SMAD4) and its favorable prognostic value. Moreover, METTL16 was under-expressed in PDA tissues and cell lines. Consistently, gain- and loss-of-function experiments indicated that it had a tumor suppressor role in vitro and in vivo. Further, gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses revealed that METTL16 may have an effect on the tumor microenvironment. Interestingly, a markedly positive association between METTL16 expression and infiltration of B cells and CD8+ T cells was observed according to the CIBERSORT and TIMER databases. Enhanced expression of immune checkpoints and cytokines was elicited in patients with over-expression of METTL16. Interestingly, decreased expression of PD-L1 was observed when upregulation of METTL16 expression occurred in MIA PaCa-2 cells, while increased expression of PD-L1 existed when downregulation of METTL16 happened in HPAF-II cells. Collectively, these findings highlight the prognostic value of METTL16 and indicate that it is a potential immunotherapy target that could be used to regulate the tumor microenvironment and promote antitumor immunity in PDA.